Efektivitas Pelaksanaan Pilkada Serentak 2020 Pada Masa Pandemi Darurat COVID-19 di Kota Dumai - Hizra Marisa; Arif Rahman Putra (JOELS: Journal of Election and Leadership, 2022)
This study discusses the implementation of the 2020 PILKADA (REGIONAL HEAD ELECTION) carried out in conditions of the Covid-19 pandemic, the implementation of the Pilkada provides challenges related to democratic practices and keeping the community safe according to good health protocols. This study aims to see how big the chances of participants in the elections. The research method is qualitative, by collecting data from mass media and social media reports. This paper will also discuss the Dumai City KPU strategy in increasing voter political participation in carrying out the PILKADA, the positive and negative impacts of continuing to carry out the PILKADA and the efforts that can be taken by the government so that the simultaneous regional elections in 2020 are carried out properly.